Olfactory Sensitivity Is Related to Erectile Function in Adult Males - Deng, Hui-yi; Feng, Jia-rong; Zhou, Wen-hao; Kong, Wei-feng; Ma, Gong-chao; Hu, Teng-fei; Luo, Shao-ge; Xi, Yu; Zhang, Yan; Yang, Qin-tai (Frontiers in Cell and Developmental Biology, 2020)
Background: The olfactory system influences human social behavior, especially in spousal selection, with vomeronasal organ (VNO) playing an important role. However, there is currently a lack of clinical research on the relationship between olfactory and erectile dysfunction (ED) in male adults. Aim: We aimed to explore the connection between olfactory sensitivity and erectile function and its possible mechanisms. Results: A retrospective analysis of 574 patients diagnosed with ED in the Department of Infertility and Sexual Medicine of the Third Affiliated Hospital, Sun Yat-sen University from 2015 to 2018, 459 patients (79.97%) without RD, and 115 patients (20.03%) with RD. Meanwhile, 201 cases of patients undergoing nasal surgery in ENT Department from 2012 to 2016, 172 cases (85.57%) without ED, and 29 cases (14.43%) with ED. Through telephone follow-up, we found that nasal congestion, nasal discharge, and hyposmia were the most common complains in VAS score. Additionally, 156 patients with RD and (or) ED in 2019 were enrolled, and 40 healthy volunteers for controls. Through Nocturnal Penile Tumescence and Rigidity (NPTR), International erectile function scale (IIEF-5), erection hardness score (EHS), VAS scale, Sniffin’ Sticks Test, we found that compared with ED patients, ED patients with RD had severe nasal discomfort and decreased erectile function(P=0.000). The olfactory sensation of patients with ED was lower than that of normal people, and patients both with ED and RD had the worst olfactory (P=0.000).The Spearman correlation analysis showed that the sense of smell was positively correlated with IIEF-5 (R=0.507, P=0.000) and EHS (R=0.341, P=0.000). Logistic regression analysis showed that whether with Olfactory Disorder (OD) or RD, age and VAS score were the risk of ED outcome, indicating that OD patients was a 16.479-fold increase in ED outcomes (P < 0.05). Conclusion: There is a significant correlation between olfactory sensitivity and erectile function in male. We were considered that perception of certain body odors may contribute to the concept of erectile function by enhanced recruitment of reward areas through the VNO. The olfactory sensitivity in patients with both ED and RD is worse than patients suffered from a single disease, exhibiting obvious superimposing effect.